2020
DOI: 10.3802/jgo.2020.31.e90
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the optimal sequence of adjuvant chemotherapy and radiation therapy in the treatment of advanced endometrial cancer

Abstract: Objective The optimal sequence of adjuvant chemoradiation in the treatment of advanced endometrial carcinoma (EC) remains unclear. We sought to evaluate the outcomes of patients treated with chemoradiation in sandwich fashion (chemotherapy-radiotherapy-chemotherapy; CRC), versus those treated sequentially (chemotherapy-radiotherapy; CR) (radiotherapy-chemotherapy; RC), to determine if there is a survival advantaged associated with a particular treatment sequence. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…We observed an increase in retroperitoneal recurrence in patients receiving adjuvant chemotherapy alone versus chemoradiation. These findings agree with existing retrospective as well as prospective data, suggesting the importance of radiation therapy in retroperitoneal disease control [13,[20][21][22]. Additionally, we observed a higher incidence of isolated positive para-aortic lymph nodes (18.1%) than previously reported in the literature.…”
Section: Discussionsupporting
confidence: 92%
“…We observed an increase in retroperitoneal recurrence in patients receiving adjuvant chemotherapy alone versus chemoradiation. These findings agree with existing retrospective as well as prospective data, suggesting the importance of radiation therapy in retroperitoneal disease control [13,[20][21][22]. Additionally, we observed a higher incidence of isolated positive para-aortic lymph nodes (18.1%) than previously reported in the literature.…”
Section: Discussionsupporting
confidence: 92%
“…In a later cohort study assessing the same group of patients, the authors also identified a better 5-year OS (62% vs. 35%) and PFS (57% vs. 35%) using subgroup analyses among stage IIIC2 patients treated with a sandwich sequence when compared with sequential chemoradiotherapy (20). In addition, McEachron et al have demonstrated OS and PFS benefits in patients with stage III-IV EC treated with sandwich therapy when compared with those treated with alternate sequences (21). In this multicenter analysis assessing 152 patients with relatively poor histology, 44% had endometrioid, 47.5% presented serous EC, and 8.5% had clear cell EC.…”
Section: Discussionmentioning
confidence: 92%
“…The sandwich sequence, comprising 2 to 4 cycles of CT followed by irradiation and subsequent CT, has shown promising results in several phase II studies and retrospective cohorts (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). However, its efficacy has been inconsistent and was further limited by small study samples, as well as heterogeneous compositions of histology and staging across studies.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, McEachron et al compared CT-RT-CT (36.8% of the population) vs. CT followed by RT (28.9%) or RT followed by CT (34.2%) in a sample of 152 patients. CT-RT-CT demonstrated superiority over CT-CR and RT-CT sequencing in terms of 3-year PFS (55% vs. 34% and 37%, respectively) and 3-year OS (71% vs. 50% and 52%, respectively) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%